Functional T cells targeting tumor-associated antigens are predictive for recurrence-free survival of patients with radically operated non-small cell lung cancer - Safi, Seyer; Yamauchi, Yoshikane; Eichhorn, Martin E.; Warth, Arne; Dienemann, Hendrik; Hoffmann, Hans (OncoImmunology, 2017)
In this prospective study, we examined postoperative follow-up and preoperative IFN-γ T cell responses against 14 non-small cell lung cancer (NSCLC)-associated antigens in the blood of 51 patients with NSCLC, 7 patients with benign pulmonary tumors, and 10 tumor-free patients by enzyme-linked immunospot assay. The phenotype and function of T cells specific for tumor-associated antigens (TAAs) in the blood or tumor tissue of 9 NSCLC patients were characterized in detail using TNF-α, IL-2, and IFN-γ cytokine capture assays. We found that circulating TAA-specific T cells were significantly enriched in NSCLC compared with tumor-free patients. The most frequently recognized TAAs were Aurora kinase A, HER2/neu, NY-ESO-1, and p53. TNF-α was the most abundant cytokine secreted by TAA-specific T cells in the blood as well as by in situ-activated tumor-infiltrating lymphocytes, most of which were effector memory cells. The absence of TAA-reactive T cells identified patients at higher risk of tumor recurrence, irrespective of tumor stage (OR = 8.76, 95% CI: 1.57-34.79, p = 0.008). We conclude that pre-existing TAA-reactive circulating T cells are a strong independent prognostic factor for recurrence-free survival. These data may help discriminating high-risk from low-risk patients, improving prognostication, and redirecting adjuvant therapy. Our findings suggest the therapeutic relevance of Aurora kinase A, HER2/neu, NY-ESO-1, and p53 as targets for immunotherapy. This study is registered on Clinicaltrials.gov with trial identification number: NCT02515760